Consumer awareness and willingness to pay for good agricultural practices-certified vegetables in Davao City, Philippines - Villaruel, Hananeel B.; Shuck, Vlademir A.; Aguinaldo, Roxanne T.; Oracion, Hermelie R.; Concepcion, Sylvia B. (2019)
The proliferation of foodborne illnesses globally and the increase in dietary concerns of consumers lead to an increased interest on food safety. At the farm level, the adoption of good agricultural practices (GAP) ensures all aspects of farming at any point from production to distribution is safely handled and free from microbial and chemical food hazards. This study assessed the consumer awareness and willingness to pay (WTP) for GAP-certified vegetables in Davao City. Vegetables considered in this study were tomato, eggplant, sweet pepper, bitter gourd, squash, and cucumber. Tobit regression model was used to analyze the factors influencing consumers' WTP for GAP-certified vegetables, employing 235 respondents who were chosen randomly. Results revealed that only 29% were aware about GAP-certified vegetables. Also, majority of the consumers (78%) were willing to pay for GAP-certified vegetables if it is made widely available in Davao City. Moreover, consumers have slightly higher WTP for GAP-certified vegetables when sold in the wet market than in the supermarket. This may be due to the fact that the prices of the vegetables sold in supermarkets are at least twice the price of the wet market. The perception that vegetables sold in the supermarket are already safe also lessens the value proposition of GAP-certified vegetables. The results also indicate that consumers were concerned about certain food safety attributes that are also covered under GAP. This study recommends that more efforts should be exerted in promoting GAP-certified vegetables, i.e., employing appropriate information dissemination and increase of production and marketing of GAP-certified vegetables.
Keywords: Mindanao studies